PENGARUH PENGETAHUAN KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN DENGAN PENGENDALIAN DIRI SEBAGAI VARIABEL MODERASI - Magfirah Hasda Nur (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to determine and analyze the impact of Financial Management Behavior which is influenced by financial knowledge on members of the North Maluku GenBI community and whether self-control can strengthen the relationship between financial knowledge and Financial Management Behavior. This study uses a questionnaire distribution technique and a quantitative analysis approach with the help of the SPSS version 28.0 for MacOs program. The results of this study partially show that financial knowledge (X1) has no effect on financial management behavior (Y). With the existence of self-control (Z) as a moderating variable, it can strengthen the relationship between financial knowledge (X) and financial management behavior (Y).